A Analisis Bahaya pada Pengrajin Anyaman Bambu - Isyeu Sriagustini; Teni Supriyani (Faletehan Health Journal, 2021)
Woven bamboo is endless and can be made into various handicrafts with high use and artistic value. But behind that, there is a long work process and possible potential hazards so that worker protection is needed. The purpose of this study was to identify the potential hazards of the work environment at each stage of making bamboo woven crafts. The research method used was descriptive observational. The research subject was bamboo weaving craftsmen and the object was all stages of the activities of making bamboo woven crafts. The results showed four main activities of making bamboo woven crafts, namely the stage of making woven materials, the stage of preparing additional woven materials, making woven products, and finishing. From each stage, four potential hazards were identified, namely: physical hazards in the form of work weather and noise; chemical hazards such as dust, smoke and applied chemicals; ergonomic hazards from non-ergonomic methods and work positions; and mechanical hazards from the materials and equipment used. The researchers concluded that at each stage of the activity of bamboo woven making there are potential hazards of the work environment that need to be considered by craftsmen and business owners. This data of identification results can be used as a database of work environment hazard control efforts.